The impact of infectious disease experience on household consumption: evidence from rural China - Han, Linlin; Xue, Xiaoling; Yu, Jinxiang (Frontiers in Public Health, 2024)
Objective The issue of low consumption among rural households in China has a longstanding history, and the experience of infectious diseases may exacerbate the existing challenges in fostering consumption growth. However, studies that characterize the impact of infectious diseases on household consumption are limited in China. This study aims to explore rural household consumption responses to infectious diseases post-assessment, and identify the underlying mechanisms. Methods A total of 1,539 rural households from China Family Panel Studies (CFPS) datasets of 2014, 2016, 2018, and 2020 were recruited as the study sample. The presence of infectious disease experience was employed as the independent variable and household consumption as the dependent variable. A panel fixed effects (FE) regression model was initially employed to identify the influence of infectious disease experiences on rural household consumption. The instrumental variable (IV) method was used to address potential endogeneity between independent and dependent variables. Robustness checks such as Propensity Score Matching (PSM) test were employed to ensure the reliability of the findings. Results The results reveal a statistically significant negative impact of infectious disease experiences on consumption over time, becoming no more significant at around 7–9 years post-disaster. This effect leads to more pronounced consumption deprivation for households with limited health insurance coverage and heightened healthcare resource constraints. The mechanism test indicates that infectious disease experiences affect the consumption levels of rural households through channels that include income constraints, the crowding-out of healthcare expenditure, and risk perception, with the precautionary savings motive acting as a moderator. Furthermore, the diminishing effect of infectious diseases on individual consumption surpasses that of natural disasters. Temporal discrepancy is observed in the impacts of infectious and chronic disease shocks on household consumption. The accumulation of liquid assets emerges as an effective strategy for households to mitigate the impact of infectious disease shocks. Conclusion The findings underscore the importance of integrating short- and long-term policies to bolster consumption capacity, strategically allocate inter-regional medical resources, and fortify the resilience of rural households against economic risks.